Síndrome de Poland, asociado a hipoplasia tubular de la aorta y neurofibromatosis tipo I en una adolescente - Teruel Ginés, Rolando; Leyva Montero, María de los Ángeles; Borjas Leyva, Raiker; Díaz Triana, Ivett (Correo Científico Médico, 2012)
Se presentó el caso de una adolescente, portadora de un síndrome de Poland en asociación con neurofibromatosis I y extensa hipoplasia tubular de la aorta que producía severa hipertensión arterial secundaria. Al examen físico había hipoplasia del músculo pectoral mayor izquierdo, mama, areola y pezón de ese lado. El brazo izquierdo estaba hipotrófico. La piel mostraba mancha café con leche, pecas axilares y neurofibromas típicos. Existía severa hipertensión con pulsos femorales imperceptibles. El riñón izquierdo no captaba el contraste en la urografía, y la tomografía multicorte contrastada puso en evidencia un neurofibroma sacro, estenosis de las arterias subclavia y renal izquierdas, y marcada hipoplasia aórtica en todo su trayecto, con calibre de 9 mm. Se hacen consideraciones etiopatogénicas y se concluyó con la certeza de lo infrecuente del padecimiento, lo extraordinariamente raro de la hipoplasia tubular aórtica, y en lo excepcional de la asociación de los tres estados patológicos. Palabras clave: síndrome de Poland, hipoplasia tubular de la aorta, neurofibromatosis ABSTRACT A 19-year-old patient carrier of a Poland’s syndrome in association with neurofibromatosis I and extended aortic tubular hypoplasia, producing severe secondary high blood pressure. The physical examination showed hypoplasia of the left pectoral’s major muscle, including the breast, areola and nipple of the same side. The left arm was hypotrophy and with less length than the right one. Many café au lait spots, freckle in the axillae and typical neurofibromas were found in the skin. There was a severe asymptomatic high blood pressure with imperceptible femoral pulse and a grade II hypertensive retinopathy. The chest x-ray showed hypoplasia of the arch of the aorta and it was evident the concentric hypertrophy of the left ventricle by the echography. The both arms x-ray showed a hypotrophy of the left radius and ulna, and the left kidney was considered as not functional with absence of the contrast uptake in the urography. The multicut contrasted tomography determinated a sacral neurofibroma, stenosis of the left subclavian and renal arteries, and aortic hypoplasia in all of its extension with 9 mm. Ethyopathogenic considerations were made, the extraordinary rare of the tubular aortic hypoplasia and in the exceptional of the association of the three pathologic states. Key words: Poland’s Syndrome, aortic tubular hypoplasia, neurofibromatosis